Zooplankton sebagai Indikator Kesuburan Perairan Kolam Budidaya Ikan - Gusmaweti Gusmaweti; Lisa Deswati; Vendri Geraldine Kurniawan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aimed to analyze the structure of zooplankton communities in former gold mining ponds for fish cultivation in Nagari Muaro, Sijunjung District, Sijunjung Regency, West Sumatra. The research method used is a descriptive survey. Determining the location for sampling zooplankton was carried out using purposive sampling. The research results showed that the overall abundance of zooplankton was found to be 18.2 ind/l, consisting of 4 phyla and several genera or types. The phyla found were, a) the Protozoa phylum with 2 genera, namely Astramoeba and the Arcella genus with an abundance of 3.2 ind/l; b) the Rotifera phylum consists of 7 genera, namely the genus Branchinus, Lycane, Keratella, Notholca, Trichoyria, Polymerurus, and the genus Habrotrocha with an abundance of 5.4 ind/l; c) phylum Crustaceae, 3 genera, namely Nauplius, Cyclops, and Daphnia with an abundance of 9.5 ind/l; d) the phylum Arthropoda has 1 genus, namely Chironomus with an abundance of 0.1 ind/l. The highest abundance was found in the phylum Crustaceae. The zooplankton diversity index at the three stations has an average value of 2.08, the evenness index has an average value of 0.83, and the zooplankton dominance index has an average value of 0.16. The results of measuring physical factors are the average turbidity of 3.53 NTU, the average water temperature is 32oC, and the average pH of water is 6. The results of measuring the average water chemical factors are water DO of 5.15 ppm, BOD of 1.77 ppm , COD was 26.45 ppm, CO2 levels were 18.29 ppm, and measured mercury (Hg) levels ranged from 0 – 0.03 ppm. Conclusion, based on the abundance of zooplankton found, the pond waters are classified as mesotrophic with a moderate level of fertility diversity. Keywords: Ex-Mining, Indicators, Ponds, Structures, Zooplankton